KONFLIK PENGELOLAAN TANAH ULAYAT DI NAGARI SUNGAI KAMUYANG: KONFLIK PENGELOLAAN TANAH ULAYAT DI NAGARI SUNGAI KAMUYANG - Redni Putri Meldianto; Jendrius; Alfan Miko (UNIB Press, 2024)
The conflict over customary land in Nagari Sungai Kamuyang reflects a complex interplay among various actors, including the Kerapatan Adat Nagari (KAN), local leaders, government officials, and external entities such as investors. This study examines the dynamics between these actors and the impact on the resolution of land disputes. A qualitative approach was used, involving in-depth interviews with key stakeholders, including representatives of KAN, local leaders, government officials, and community members. Secondary data were gathered from relevant documents, reports, and previous studies on customary land conflicts in Minangkabau. The findings reveal a significant power imbalance between the local community and external actors, such as the government and investors. The dualism within KAN has further complicated the conflict resolution process, with competing factions influencing decision-making and contributing to a lack of clarity in enforcing customary laws. The government’s policies often conflict with traditional rights, exacerbating tensions. The community faces increasing pressure from external economic interests, threatening their cultural heritage and social structure. The conflict over customary land in Nagari Sungai Kamuyang illustrates the challenges of balancing traditional rights with pressures from modern development. The duality within KAN and the lack of cohesive support from the government hinder effective conflict resolution. An inclusive approach involving constructive dialogue and recognising customary and modern legal frameworks is crucial for achieving a fair and sustainable resolution. Resolving the customary land conflict in Nagari Sungai Kamuyang requires addressing the power imbalances, bridging gaps between traditional and modern legal systems, and ensuring that community voices are adequately represented in decision-making processes.